2020
DOI: 10.1038/s41598-020-77236-2
|View full text |Cite
|
Sign up to set email alerts
|

Jitter-free 40-fs 375-keV electron pulses directly accelerated by an intense laser beam and their application to direct observation of laser pulse propagation in a vacuum

Abstract: We report the generation of ultrashort bright electron pulses directly driven by irradiating a solid target with intense femtosecond laser pulses. The duration of electron pulses after compression by a phase rotator composed of permanent magnets was measured as 89 fs via the ponderomotive scattering of electron and laser pulses, which were almost at the compression limit due to the dispersion of the electron optics. The electron pulse compression system consisting of permanent magnets enabled extremely high ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…At present, these particle beams are predominantly generated by conventional accelerators, and the full potential of particle beam generation using lasers has not yet been realized in terms of beam quality and controllability. However, as described in this paper, further advances are expected in the future, such as the generation of ultrashort electron pulses [23]. Finally, an important feature of laser-generated quantum beams is that all quantum beams can be generated using a single laser, such that each quantum beam can be in perfect synchronization.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At present, these particle beams are predominantly generated by conventional accelerators, and the full potential of particle beam generation using lasers has not yet been realized in terms of beam quality and controllability. However, as described in this paper, further advances are expected in the future, such as the generation of ultrashort electron pulses [23]. Finally, an important feature of laser-generated quantum beams is that all quantum beams can be generated using a single laser, such that each quantum beam can be in perfect synchronization.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, it has been confirmed that the electron deflection method using lasergenerated/accelerated electron pulses is useful for measuring electromagnetic fields that change at high speed. Recently, we have also succeeded in capturing a laser pulse traveling in a vacuum using this electron deflection method [23].…”
Section: Generation Of Intense Terahertz Surface Wavesmentioning
confidence: 99%
“…Ultrafast lasers that enable the generation of ultrashort energetic pulses have become indispensable tools for a variety of applications, such as industrial fabrication [1,2], biomedical diagnosis [3,4], controllable processing of materials [5,6], pulse measurement [7,8], gasphase thermometry, and species concentration measurements [9]. One common method for producing ultrashort pulses in ultrafast lasers is the passive method that introduces a modulation of the intracavity field by placing a saturable absorber (SA) element in the cavity [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%